2018
DOI: 10.1371/journal.pone.0207932
|View full text |Cite
|
Sign up to set email alerts
|

A model investigating environmental factors that play a role in female fecundity or birth rate

Abstract: ObjectiveOver 12% of women in the United States have reduced fertility and/or fecundity. Environmental factors, such as temperature, and socioeconomic factors have been implicated in reducing female fecundity. The purpose of this study is to investigate the effect of environmental factors coupled with socioeconomic factors on birth rate at the country-level. We use birth rate as a proxy for female fecundity. This will enable us to identify the most important factors affecting female fecundity.MethodsUsing coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Another study found a U-shaped distribution between weight and later fertility, with fat determining the time of menarche, indicating that those on the extremes (very underweight or very overweight) are at risk for fertility issues and potentially alterations in timing of menarche [49]. A study on female fertility at the country level using birth rates and average country statistics on body mass index (BMI) found that a country's BMI was a strong predictor for a country's fertility rate [21].…”
Section: Growth/nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found a U-shaped distribution between weight and later fertility, with fat determining the time of menarche, indicating that those on the extremes (very underweight or very overweight) are at risk for fertility issues and potentially alterations in timing of menarche [49]. A study on female fertility at the country level using birth rates and average country statistics on body mass index (BMI) found that a country's BMI was a strong predictor for a country's fertility rate [21].…”
Section: Growth/nutritionmentioning
confidence: 99%
“…Other single-factor studies have evaluated factors present at a broader scale, using climate variables like regional temperature [18,19] and altitude [20]. One recent study demonstrated the potential for interdependence between these types of factors when assessing female fecundity [21], opening the possibility for a similar dynamic to exist in other outcomes related to reproduction, such as menarche. There is limited literature to suggest an underlying mechanism for the changes seen in timing of menarche over time.…”
Section: Introductionmentioning
confidence: 99%
“…Housing prices may also be an essential factor affecting the birth rate, and this manifestation can be expressed through intuitive mathematical simulations on a material basis. Female fertility also cannot be ignored, which may be related to air pollution levels or environmental factors such as temperature [9,10]. The decline in human fertility is due to changes in the natural environment and not just sociological changes [11].…”
Section: Introductionmentioning
confidence: 99%